(untitled) (Research, Society and Development, 2021)
In 2019, a pathology called COVID-19 appeared, caused by SARS-COV 2 (new coronavirus) that has a viral origin with high transmission and contagion power. The main means of contamination are through coughing, sneezing, physical contact and released secretions. The main means of reducing dissemination is through the use of masks, social isolation, social distance and hand hygiene with soap and water or 70% alcohol. Thus, it is worth emphasizing the importance of analyzing the main emotional impacts that this disease caused to nursing professionals. Objective: to analyze, in the light of the literature, the main emotional impacts caused by the new coronavirus pandemic on nursing professionals. Methodology: This is a literature review research, with a descriptive character and a quantitative approach. Results: 15 articles were chosen on the proposed topic, in which the importance of special care for health professionals who suffer from psychological impacts was observed, so that they contribute to the care of the population in general. Final considerations: COVID-19 is a pathology that has great impacts on the mental health of health professionals, due to the greater risk of contamination and transmissibility.